2013
DOI: 10.1158/1055-9965.epi-13-0142
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Leukocyte Telomere Length and Risk of Renal Cell Carcinoma

Abstract: Background It has been hypothesized that genomic instability related to telomere dysfunction may contribute to carcinogenesis. There is some evidence from case-control studies suggesting that short leukocyte telomere length (TL) may be associated with an increased risk of renal cell carcinoma (RCC); however, this association has not been investigated prospectively. Methods We conducted a nested case-control study (209 cases, 410 controls) of RCC risk in relation to pre-diagnostic leukocyte TL in the Prostate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
2
14
1
Order By: Relevance
“…Results of studies of leukocyte telomere length and risk of renal cell carcinoma (RCC) have been inconsistent. Two small hospital-based case-control studies reported inverse associations between telomere length and risk of RCC [10,11], whereas no significant evidence of an association was observed in a larger population-based case-control study [12] and two cohort-based investigations using prediagnostic samples [13,14]. In contrast, longer leukocyte telomere length has been associated with reduced RCC survival [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of studies of leukocyte telomere length and risk of renal cell carcinoma (RCC) have been inconsistent. Two small hospital-based case-control studies reported inverse associations between telomere length and risk of RCC [10,11], whereas no significant evidence of an association was observed in a larger population-based case-control study [12] and two cohort-based investigations using prediagnostic samples [13,14]. In contrast, longer leukocyte telomere length has been associated with reduced RCC survival [15].…”
Section: Introductionmentioning
confidence: 99%
“…Leukocyte telomere length measurements in case-control studies, using postdiagnosis blood samples, may have been influenced by effects of the disease. All studies measured telomere length from a single time point, which may not adequately reflect telomere length status in the etiologically relevant time window, and were susceptible to confounding from RCC risk factors that may be associated with telomere length such as smoking [13,18] and obesity [19]. Furthermore, qPCR-based measurements of telomere length are sensitive to preanalytic factors such as DNA source material and extraction method [12,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Telomere shortening has been proved to be a risk factor in many sporadic and hereditary cancers, including Lynch syndrome, hereditary prostate cancer, familial, and sporadic ovarian cancer. As to RCC, two hospital‐based case–control studies demonstrated that short leukocyte telomere length was associated with increased sporadic RCC risk, while a large population‐based study drew different conclusions . Svenson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Critically short telomeres lead to genetic instability and increase risks of age‐related disease including cancers . Peripheral blood leukocyte telomere length has been reported to be a potential biomarker of tumor risk for various types of familiar and sporadic tumors, including hereditary non‐polyposis colorectal cancer(Lynch syndrome), hereditary prostate cancer, familial and sporadic ovarian cancer, renal cell carcinoma and pancreatic cancer . VHL disease seems similar to some hereditary disease such as Lynch syndrome, and shorter telomere length contributes to the earlier onset age in the next generations than their parental generations within VHL families.…”
Section: Introductionmentioning
confidence: 99%
“…36 Hoffman et al also conducted two case-control studies, one of them prospective. 63 In both studies, no differences between cases and controls' TL were found, as well as no associations between TL and tumor stage. 63,64 Interestingly, these two studies are the ones which display the biggest sample size of all the case-control studies.…”
Section: Literature Review and Data Collectionmentioning
confidence: 74%